La polémique médiatique — le cas Darrieussecq - Kotowska, Katarzyna (Romanica Silesiana)
Twice accused of plagiarism, Marie Darrieussecq repeats that for a writer, this kind of accusation is equal to a murder attempt. The case of Darrieussecq is a good example of how various media profit from quarrels between contemporary writers. In 1998, Marie NDiaye accused Darrieussecq of “monkeying” in her novel Naissance des fantômes. Later, in 2007, one of Darrieussecq’s colleagues from the P.O.L. Publishing House, Camille Laurens, referred to Tom est mort as ’psychological plagiarism’. This conflict was escalated by the media and followed a certain pattern: there was an accusation, an accuser and the victim. Key words: Plagiarism, Darrieussecq, media.